Odor Recognition Memory in Parkinson's Disease: A Systematic Review - Eek, Tom; Larsson, Maria; Dizdar, Nil (Frontiers in Aging Neuroscience, 2021)
Olfactory impairment is a central non-motor symptom in Parkinson’s disease (PD). Previous studies have demonstrated that olfactory dysfunction is associated with mental illness and impaired cognition. The frequently investigated olfactory functions are odor detection, discrimination, and identification. However, few studies have focused on odor recognition memory (ORM). ORM tasks involves episodic memory which therefore can facilitate the detection of dementia among patients with PD and consequently adjust their treatment. Thus, the aim of this systematic review is to summarize the existing research on ORM in PD. Databases and reference lists were used for data collection. Studies were included in the review if they met the eligibility criteria derived from the PICOS-framework. Quality evaluation of the studies was based on the STROBE-statement. Six studies with small samples were included in the analysis which demonstrated the scarce research on the subject. The studies targeting ORM were heterogenous and involved two main tasks: odor recognition and odor matching. The synthesis of the data demonstrated that PD patients performed significantly lower than controls on both tasks, especially on odor matching task. Only the odor recognition task exhibited a difference between patients with PD versus Alzheimer’s disease (AD). PD patients performed significantly better than AD patients. The findings based on the available limited data support the notion that odor recognition task can be of importance in identifying Parkinson’s disease dementia (PDD). To investigate this hypothesis, future research needs to include larger samples of PD, PDD and AD patients executing the same odor recognition task.